Stitching the fabric of life: Refugee stories and the non-refugee narrator. A creative non-fiction manuscript and exegesis - Sayer, Rosemary (Curtin University, 2019)
This thesis is presented as a work of creative non-fiction and an accompanying exegesis. Together, they explore how narrative identity can be developed by people of a refugee background through a collaborative process of working with a non-refugee narrator. In my creative non-fiction work, Stitching the fabric of life, I collaborate with 11 women and three men to create a series of life stories to challenge the over-generalised notion of “the refugee experience”.